The Invisible Actors of Forced Migration: Male Refugees in The Context of Representation and Gender - Filiz Göktuna Yaylacı; Mehmet Can Çarpar (Journal of Economy Culture and Society)
In recent years, forced migration, which is pretty important in Turkey’s agenda, is discussed by different disciplines, especially in politics, in different frameworks, such as integration, education, security, health and gender. When considering the studies that examining forced migration from a gender perspective, however, it is seen that the studies mostly focus on women because they are more exposed to social problems. This situation, which is added to the representation of refugee masculinity as perpetrators in the host societies, mostly by media, causes the experience of male refugees to be invisible, and the social aid practices directed towards refugees are less susceptible to the problems of men. In this context, the main purpose of this research is to analyze the problems of male refugees that cannot be seen because of their negative representations, and to discuss them based on social aid policies. The study was designed as a phenomenological qualitative research. Data were collected from 17 male refugees and five specialists who are working in the field of humanitarian aid, by semi-structured interview technique. The findings of the research show that, like refugee women, some refugee men are exposed to various social problems, such as violence, discrimination, poverty, unemployment and labor exploitation. Another remarkable finding in the study is that, despite their disadvantages, single and unaccompanied refugee men were excluded from the field of social aid and migration regulations.